LEGAL REVIEW OF CANCELLATION OF AGREEMENT BORROW FOR LAND ORDERLY - Muhammad Fadly; Mhd Syukran Yamin Lubis (Inspiring Law Journal, 2025)
This research is motivated by the position of the Curator who has the authority in the management and settlement of bankrupt assets, thus demanding independence as a fundamental principle to guarantee justice and protection of the interests of creditors and debtors. Article 15 paragraph (3) of Law Number 37 of 2004 concerning Bankruptcy and PKPU requires the Curator to be independent, honest, and impartial, but does not provide a clear definition or indicator regarding the phrase